2020
DOI: 10.1002/pat.5111
|View full text |Cite
|
Sign up to set email alerts
|

Electrospinning of polyvinyl alcohol/chitosan/hyaluronic acid nanofiber containing growth hormone and its release investigations

Abstract: A wound is defined as an interruption in the integrity of skin and mucus tissue. There are challenges in the treatment of some lesions, such as diabetic ulcers, burn injuries and pressure ulcers. Wound dressing is one of the new methods used to treat these types of ulcers. Nanofibers are very suitable structures for wound healing due to their prevention of pathogen penetration into the wound environment and providing sufficient gaseous exchange, absorption of wound secretions and controlled release of the drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 17 publications
1
17
0
Order By: Relevance
“…The time required for spinning polymers in previous studies was generally above one hour. This is despite the fact that gelatin and PLA polymers were spun in 10 min in the present study and the desired textiles were obtained [ 51 , 52 ]. The antibacterial test showed that silver nanoparticles, in addition to being able to exert their effect in the open environment, can also express their antibacterial properties among nanofibers and prevent the growth of bacteria.…”
Section: Discussionmentioning
confidence: 93%
“…The time required for spinning polymers in previous studies was generally above one hour. This is despite the fact that gelatin and PLA polymers were spun in 10 min in the present study and the desired textiles were obtained [ 51 , 52 ]. The antibacterial test showed that silver nanoparticles, in addition to being able to exert their effect in the open environment, can also express their antibacterial properties among nanofibers and prevent the growth of bacteria.…”
Section: Discussionmentioning
confidence: 93%
“…PVA‐chitosan‐ hyaluronic acid (HA) dressings crosslinked with glutaraldehyde and containing growth hormone were prepared by electrospinning. The resultant dressing is hydrophilic, non‐toxic, and provides a sustained‐release mechanism in which 64% of growth hormone was released from the nanofibers 2 days after the initial burst release [34] . Barzegar et al (2021) developed a core‐shell nanofiber scaffold composed of PVP‐maltodextrin as a shell and PVA‐chitosan as a core for a nanofiber dressing.…”
Section: Preparation Methods Of Pva‐based Wound Dressingmentioning
confidence: 99%
“…The resultant dressing is hydrophilic, non-toxic, and provides a sustained-release mechanism in which 64% of growth hormone was released from the nanofibers 2 days after the initial burst release. [34] Barzegar et al (2021) developed a core-shell nanofiber scaffold composed of PVP-maltodextrin as a shell and PVA-chitosan as a core for a nanofiber dressing. The manufactured nanofiber dressing contains antibacterial substances, has improved physical properties, and has antioxidant and antibacterial effects.…”
Section: Chitosanmentioning
confidence: 99%
See 2 more Smart Citations